Effects of vermicompost on growth and leaf biomass yield of stevia and post harvest fertility status of soil - Zaman, MM; Chowdhury, MAH; Islam, MR; Uddin, MR (Journal of the Bangladesh Agricultural University, 2016)
In view of the growing awareness about eco-friendly organic farming, vermicompost (VC) could be a very good option for increasing crops yield. The organic carbon in VC releases nutrients slowly and steadily into the system and enables the plant to absorb these nutrients. To assess the effect of VC on soil fertility, growth and yield of stevia in acid and non-calcareous soils, an experiment was undertaken in the net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh, during February to May, 2012. Four levels of VC viz. 0, 5, 7.5 and 10 t ha-1 in two contrasting soils (Acid and Non-calcareous) were examined following CRD with three replications. Growth and yield attributes such as plant height, branch and leaf number, leaf area, fresh and dry weight of leaves were significantly influenced by different levels of VC. All the plant parameters increased with the advancement of growth period as well with increased rate of VC up to 7.5t ha-1 and then declined with further additions. The leaf biomass yield was 335% and 338% higher in acid soil and in non-calcareous soil, respectively over control. The overall performance of non-calcareous soil was superior to acid soil in terms of both plant and soil parameters studied. The acidity of both soils significantly decreased with the increased application of VC ranging from 4.9 to 5.7 in acid soil and 6.5 to 7.2 in non-calcareous soil. Total N, available P, exchangeable K, Ca, Mg, available S, Zn, B were also significantly increased with the increased levels of VC up to its highest level (VC @ 10t ha-1) in both soils. Thus the results suggest that VC @ 7.5t ha-1 should be applied for getting maximum leaf biomass yield of stevia and 10t ha-1 for increasing the fertility of both soils under the agro-climatic conditions of the studied area. J. Bangladesh Agril. Univ. 13(2): 169-174, December 2015